Fusion rate and complications of oblique lumbar interbody fusion and transforaminal lumbar interbody fusion in the treatment of lumbar degenerative diseases: a meta-analysis - Xiao, Xun; Duan, Heng; Pan, Xin; Zhao, Hua (Frontiers in Surgery, 2024)
Background: At present, there is still some controversy about the efficacy of oblique lumbar interbody fusion (OLIF) and transforaminal lumbar interbody fusion (TLIF) in the treatment of lumbar degenerative diseases. Aim: This study compared the application effects of OLIF and TLIF in lumbar degenerative diseases by reviewing the literature and using meta-analysis. Methods: We included randomized controlled trials and cohort studies comparing TLIF and OLIF in the treatment of lumbar degenerative diseases. Search for "intervertebral disc degeneration", "spinal fusion", "lumbar vertebrae ", and other words in Pubmed, Embase, and Cochrane Library databases. The search date was set from the establishment of the database to October 2023. Two authors independently conducted document screening, data abstraction, and qualitative assessment. Meta-analysis was performed and adapted to RevMan5.3 software. The odds ratio (OR), weighted mean difference (WMD), and 95% Cl were calculated by adopting a fixed-effect model (FEM) or a random-effect model (REM). Results: A total of 18 cohort studies were included, with 1550 patients, including 806 patients receiving TLIF (TLIF group) and 744 patients receiving OLIF (OLIF group). There were no significant differences in fusion rate [OR=1.58(0.95,2.64), P=0.08], complication rate [OR=1.25(0.93,1.68), P=0.14], and visual analog scale for back pain (VAS-BP) [WMD=0.00(-0.13,0.14), P=0.96] between the two groups. Compared with the TLIF group, the OLIF group had a lower Oswestry disability index (ODI) [WMD=-0.62(-1.03,-0.20), P=0.003], higher foramen height (FH) [WMD=2.03(1.42,2.46), P<0.001], higher disc height (DH) [WMD=1.69(1.17,2.22), P<0.001], and shorter length of stay (LOS) [WMD=-1.80(-2.55, -1.05), P<0.001].In the treatment of lumbar degenerative diseases, compared with TLIF, OLIF has more advantages in improving lumbar function, restoring FH and DH, and shortening LOS, while the two are comparable in fusion rate, complication rate, and improvement of lumbar pain. Because of the small amount of included research and the unclear assessment of the risk of bias. In the future, high-quality, large-sample randomized controlled studies are still needed to prove it.